2006
DOI: 10.1038/sj.pcan.4500884
|View full text |Cite
|
Sign up to set email alerts
|

Germline BCL-2 sequence variants and inherited predisposition to prostate cancer

Abstract: Apoptosis is an essential physiological process that regulates cellular proliferation. Here, we explored the effect of DNA sequence variation within the BCL-2 gene on prostate cancer susceptibility in three clinical populations, consisting of 428 African Americans, 214 Jamaicans and 218 European Americans. We observed a 70% reduced risk for prostate cancer among the European Americans who had possessed two copies of a promoter variant À938C/A. Additionally, common BCL-2 haplotypes appeared to influence prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…Bcl-2 expression has also been implicated in the pathogenesis of cancers [37, 38], and the expression of Bcl-2 to Bax ratio seems to be important in determining both in vitro and in vivo response to chemotherapeutic drugs [39]. Recently, variant allele of Bcl-2 −938C>A was found to be associated with reduced prostate cancer risk in Caucasians in a small case-control study, possibly due to the elimination of an Sp1 binding site, a downregulation of Bcl-2 mRNA transcript levels, and unregulated programmed cell death [40], which is consistent with what we found in the current study (the variant A allele carriers were associated with high-AC phenotype that may help eliminating possible malignant cells).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 expression has also been implicated in the pathogenesis of cancers [37, 38], and the expression of Bcl-2 to Bax ratio seems to be important in determining both in vitro and in vivo response to chemotherapeutic drugs [39]. Recently, variant allele of Bcl-2 −938C>A was found to be associated with reduced prostate cancer risk in Caucasians in a small case-control study, possibly due to the elimination of an Sp1 binding site, a downregulation of Bcl-2 mRNA transcript levels, and unregulated programmed cell death [40], which is consistent with what we found in the current study (the variant A allele carriers were associated with high-AC phenotype that may help eliminating possible malignant cells).…”
Section: Discussionmentioning
confidence: 99%
“…African Americans were recruited from Washington, DC (N = 106) and Columbia, S.C. (N = 426). African American and Caribbean subjects were recruited for various cancer genetic studies [36], [37], [38], [39]. West African samples (N = 508), included 48 Bini from Edo State, Nigeria; 64 Ibo from Enugu State, Nigeria; 18 Hausa from Jos, Nigeria, 49 Yoruba from Ibadan, Nigeria; 61 Yoruba from Lagos, Nigeria; 28 Urhobo and 21 Itsekiri from the Warri Delta region of Nigeria; 34 Kru from Freetown, Liberia; 47 Mende and 34 Temne from Freetown, Sierra Leone [38]; 19 Mandinka from Dakar, Senegal; and 85 Bamileke from Yaounde, Cameroon [38], [40], [41], [42].…”
Section: Methodsmentioning
confidence: 99%
“…The A allele is associated with higher expression levels of Bcl‐2 in different malignant tissues, and −938C>A genotypes were associated with survival of patients suffering from the corresponding cancers,26–28 including a most recent report on the correlation of the −938C>A promoter SNP with biochemical recurrence after radical prostectomy in a small cohort of Japanese men 29. Furthermore, Kidd et al showed an association of this polymorphism with risk for prostate cancer in a small cohort 30. However, a study in CLL patients has reported no association of genotypes with BCL2 mRNA levels and overall survival 31…”
mentioning
confidence: 99%